Regional Pro Bon Conference Held at Hilton Hotel - Watkins, Howard::::::::: (1989)
Former and current Fresno-Merced Counties Legal Services (F-MCLS) Executive Directors: LeRoy Cordova and Joe Romero Fresno-Merced Counties Legal Services=Fresno-Merced Counties Legal Service